114k views
1 vote
Can anyone help please????

Can anyone help please????-example-1
User Tobias Xy
by
5.3k points

1 Answer

6 votes

Answer:

Option A.
(f_of^(-1))(-2)=-2

Explanation:

Point to remember while solving the question of function,


(f_of^(-1))(x)=x

Here, 'f' is the parent function and
f^(-1) is the inverse of the function 'f'.

So for the given function,

f(x) = 2x - 2


(f_of^(-1))(x)=x

For x = -2


(f_of^(-1))(-2)=(-2)

Therefore, Option A will be the correct answer.

User Kstepien
by
5.2k points